2011
DOI: 10.1111/j.1600-0706.2010.19134.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond species area curves: application of a scale‐free measure for spatial variability of species richness

Abstract: We report a novel pattern in species richness, complementary to the well‐known species–area relationship. We show that, as sample area increases, the variation in relative richness decreases among otherwise comparable spatial units. This pattern holds for southern African birds, French birds, Cape Proteaceae and the trees of Barro Colorado Island. We propose a scale‐free method for quantifying this pattern by measuring the multifractal intensity of species richness, which is the multi‐scale tendency of adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The symmetric pattern was not observed in the regular cases (Fig. ) because the negative part ( q < 0) analyses numbers close to 0, and the logarithm (eqn ) enhances the differences between small numbers (Laurie & Perrier ). Thus, the difference ∆ D q = ¦ D q – D 0 ¦ is greater for q < 0.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The symmetric pattern was not observed in the regular cases (Fig. ) because the negative part ( q < 0) analyses numbers close to 0, and the logarithm (eqn ) enhances the differences between small numbers (Laurie & Perrier ). Thus, the difference ∆ D q = ¦ D q – D 0 ¦ is greater for q < 0.…”
Section: Resultsmentioning
confidence: 89%
“…Ranges of q between −10 and 10 or narrower are generally used (Yakimov et al . ; Laurie & Perrier ; Saravia, Giorgi & Momo ; Wei et al . ), but sometimes the applied range has been wider (Saravia, Giorgi & Momo ).…”
Section: Resultsmentioning
confidence: 99%
“…For the uniform SAD we expected D SAD 0 to be around 0.5, following a symmetric pattern around q = 0, as all species have the same abundance and occupy the same area. The symmetric pattern was not observed in the regular cases ( Figure 2) because the negative part (q < 0) analyzes numbers close to 0 and the logarithm (equation 5) enhances the differences between small numbers (Laurie & Perrier 2011). Thus the difference…”
Section: Calculation Of Power and Type I Errormentioning
confidence: 87%
“…When q is larger in its absolute value, For the uniform SAD we expected D SAD 0 to be around 0.5, with a symmetric pattern with small deviations around this value, as all species have the same abundance and occupy the same area. The symmetric pattern was not observed in the regular cases ( Figure 2) because the negative part (q < 0) analyzes numbers close to 0 and the logarithm enhances the differences between small numbers (Laurie & Perrier 2011). Thus the…”
Section: Resultsmentioning
confidence: 87%
“…I talk of high power when its value is 0.75 or higher, and low power when it is 0.5 or lower. between -10 and 10 or narrower are generally used (Yakimov et al 2008;Laurie & Perrier 2011;Wei et al 2013) but sometimes the applied range has been wider . I started using a q range of -24 to 24, and found that for this range type I error rates were, in all cases, higher than the nominal significance level α = 0.5 (Appendix table 4).…”
Section: Statistical Power and Type I Errorsmentioning
confidence: 99%